Einsatzbereiche und Einsatzgrenzen von Straßenumgestaltungen nach dem "Shared Space"-Gedanken. - (:unkn) unknown (My University, 2015)
Verkehrsbereiche nach dem "Shared Space"-Ansatz sollen zu einer Verbesserung der Sicherheit und der Aufenthaltsqualität von innerörtlichen Straßenräumen führen. Anhand von 17 Fallbeispielen untersuchte die Bundesanstalt für Straßenwesen (BASt) die Einsatzbereiche und -grenzen von Straßenumgestaltungen mit ähnlichen Gestaltungsansätzen. Die Forschungsergebnisse erlauben über eine verkehrsrechtliche Einordnung hinaus klare Handlungsempfehlungen zur optimierten Gestaltung.

Traffic zones designed in accordance with the shared-space concept are intended to improve safety and the quality of life in urban street areas. Based on 17 case examples, the Federal Highway Research Institute (BASt) has analysed the application areas and limits of street redesigns using similar design approaches. In order to successfully implement the "shared-space" concept, a coordinated planning, construction and operation is required - particularly in relation to the interaction of the zone planning and the traffic regulations concerning street signs. On the basis of the research findings, an updated version of the "Information on street environments with particular crossing requirements - Application possibilities of the "shared-space concept"" document has been drawn up.
Keywords: Individualverkehr; Stadtverkehr; Infrastruktur; Stadtraum; Straßenraum; Raumnutzung; Funktionsmischung; Fahrradinfrastruktur; Shared Space; Mischnutzung; Mischfläche; Aufenthaltsqualität